EDUKASI RESILIENSI DIRI DAN MANAJEMEN STRES: MENYIAPKAN MENTAL CALON TENAGA KERJA VOKASI DI SMK YPWKS CILEGON - Cokorda Agung Wibowo; Veronika Joan Jasmine (Yayasan Education and Social Center, 2026)
Massive industrialization in the Cilegon region demands vocational high school (SMK) graduates who are not only mechanically proficient but also psychologically resilient. Transition shock is a prevalent phenomenon among vocational graduates due to the structural disparity between high job demands in the heavy industry sector and low personal resources. This Community Service (PkM) program aims to enhance work readiness by strengthening self-resilience and stress management among 12th-grade students at SMK YPWKS Cilegon prior to entering the Industrial Work Practice phase and professional recruitment. The intervention utilized a Blended Method approach, integrating Interactive Lectures as cognitive transmission agents and role-play-based Focus Group Discussions (FGD) as affective incubation agents. Effectiveness was evaluated through a quantitative pre-test and post-test design involving 40 participants from technical and administrative vocational programs. Empirical data analysis revealed significant improvements: cognitive understanding of stress literacy surged from an average score of 59.5 to 74.3; practical coping mechanism skills increased from 46.2% to 86.3%; and psychological well-being escalated from 91.00 to 107.63. This approach effectively reduced destructive anxiety and transformed mental vulnerability into adaptive resilience. The urgency of resilience is universal, relevant for both field workers and administrative staff. It is recommended that this psychoeducational module be integrated into the vocational counseling curriculum as an upstream Talent Pipeline Management instrument.